Macro-anatomical investigations on skeletons of otter (Lutra lutra). III. Skeleton axiale - Yilmaz, Sadik; Dinç, Gürsel; Toprak, Burhan (My University, 2000)
The aim of this study was to investigate the axial skeleton of otters (Lutra lutra). The important features of the skull as observed in this study were as follows: Tympanic bulla was well developed. Zygomatic process of the frontal bone and the supraorbital foramen was absent. Infraorbital foramen was very well developed. Dental formula was 2(I3/3, C1/1, P3/3, M2/2)=36. Mental foramens and the angular process of mandible were present. Vertebral formula was found as C7, Th14, L6, S3, Ca18. The eleventh vertebra of the thoracic vertebra was found as anticlinal vertebra. The accessory processes were caudally located on all lumbal vertebrae. The auricular surface of sacral bone was faced laterally and spinous processes were not fused. Haemal arches were present on ventral surfaces of the caudal ends of the bodies of the third to seventh caudal vertebrae. There were fourteen pairs of ribs. The first nine ribs were sternal, and four ribs were asternal. The last rib was floating. The dorsal half of ribs (os costale) was almost round in shape and the ventral half of ribs was flat in shape. The sternum was cylindrical.
Keywords: Anatomy; Axial skeleton; Lutra lutra; Otter